Online work adjustment in the sustainable development context during COVID-19 pandemic: A systematic literature review - Azizan Morshidi; Kee Y. Sabariah Kee Mohd Yussof; Rizal Zamani Idris; Rafiq Idris; Azlan Abas (Inderscience Enterprises Ltd., 2022)
This paper aims to systematically analyse and synthesise the contemporary literature on fundamental contextual issues impacting online work adjustment during the COVID-19 pandemic and to identify future research priorities in these fields, in the light of relevant perspectives of Sustainable Development Goals (SDGs) and Fourth Industrial Revolution (IR 4.0). This research used the preferred reporting items for systematic reviews and meta-analyses (PRISMAs) design approach to conduct a systematic literature review. Three academic databases, namely Scopus, ScienceDirect and Google Scholar, were utilised. The findings emphasised the importance of current research distribution, contextual issues, and thematic analysis outcomes, which recommend an essential future research agenda on online work adjustment during and after the COVID-19 pandemic.